2023
DOI: 10.3390/pharmaceutics15010216
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Nanoparticles Functionalized with Antibodies for Anticancer Drug Therapy

Abstract: Nanotechnology takes the lead in providing new therapeutic options for cancer patients. In the last decades, lipid-based nanoparticles—solid lipid nanoparticles (SLNs), nanostructured lipid carriers (NLCs), liposomes, and lipid–polymer hybrid nanoparticles—have received particular interest in anticancer drug delivery to solid tumors. To improve selectivity for target cells and, thus, therapeutic efficacy, lipid nanoparticles have been functionalized with antibodies that bind to receptors overexpressed in angio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 122 publications
0
25
0
Order By: Relevance
“…It is worth mentioning that in comparison with other targeting ligands, antibodies are considered one of the most effective approaches in different diseases (53). However, even after 3 decades the antibodytargeted nanoparticles have not been successfully translated into clinics yet (56,57), and several preclinical considerations should be taken into account to increase the success in the clinical translation of targeted nanoparticles (58,59). Regarding Doxil as the first FDA-approved nanomedicine, despite improvements in PK, one of the challenges is enhancing the therapeutic efficacy of Doxil compared to a free DOX.…”
Section: Biodistribution Of Targeted and Non-targeted Doxilmentioning
confidence: 99%
“…It is worth mentioning that in comparison with other targeting ligands, antibodies are considered one of the most effective approaches in different diseases (53). However, even after 3 decades the antibodytargeted nanoparticles have not been successfully translated into clinics yet (56,57), and several preclinical considerations should be taken into account to increase the success in the clinical translation of targeted nanoparticles (58,59). Regarding Doxil as the first FDA-approved nanomedicine, despite improvements in PK, one of the challenges is enhancing the therapeutic efficacy of Doxil compared to a free DOX.…”
Section: Biodistribution Of Targeted and Non-targeted Doxilmentioning
confidence: 99%
“…Recently, the biofunctionalization of nanoparticles has attracted the attention of many researchers because of their biocompatibility, biodegradability, eco-friendly quality, and low cost . Biofunctionalization of nanoparticles has been achieved by using bioinspired ligands, phytochemicals, and bioresources such as plants, algae, bacteria, microorganisms, etc. , Nanomaterials are functionalized with different types of bioreceptor molecules, including antibodies, aptamers, peptides, and enzymes for biomedical applications. In addition, Table summarizes the selectivity, modification, stability, and sensing properties of three bioreceptor molecules for their suitability in different optical readout techniques.…”
Section: Nanomaterials Functionalization With Bioreceptorsmentioning
confidence: 99%
“…On the other hand, the treatment of Kaposi's sarcoma and breast cancer is made possible by the liposomal formulation of anti-cancer drugs such as doxorubicin (DOX) and daunorubicin (DU) [28,29]. It has also been observed that a PEGylated liposomal formulation of DOX (MCC-465) targets metastatic stomach cancer [30], and melanoma cells also show increased intracellular absorption of the liposomal formulation of DOX in comparison to the free DOX that leads to the destruction of cancer cells [31]. A recent study investigated the in vivo anti-cancer efficacy of mycophenolic acid (MPA) and quercetin (QC) co-administered using liposomal nanoparticles (LNPs).…”
Section: Lipid-mediated Nanoformulations Of Anti-cancer Drugsmentioning
confidence: 99%